Implementation of a New Food Picture Database in the Context of fMRI and Visual Cognitive Food-Choice Task in Healthy Volunteers - Gautier, Yentl; Meurice, Paul; Coquery, Nicolas; Constant, Aymery; Bannier, Elise; Serrand, Yann; Ferré, Jean-Christophe; Moirand, Romain; Val-Laillet, David (Frontiers in Psychology, 2019)
This pilot study aimed at implementing a new food picture database in the context of fMRI cognitive food-choice task, with an internal conflict or not, in healthy normal-weight adults. The database contains 170 photographs including starters, main courses and desserts, presents a broad-spectrum of energy content, and is provided with portion weight and nutritional information. It was tested in sixteen participants who evaluated the energy density and gave a liking score for all food pictures via numerical scales. First, volunteers were segregated in two groups according to their eating habits according to a Food Consumption Frequency Questionnaire (FCFQ) to assess whether the database might elicit different appreciations according to individual eating habits. Second, participants underwent fMRI cognitive food-choice task (Van der Laan et al., 2014), using our picture database, in which they had to choose between high- (HE) versus low-energy (LE) foods, under a Similar Liking condition (SL, foods with similar hedonic appraisals), or a Different Liking condition (DL, foods with different hedonic appraisals). Participants evaluated correctly the caloric content of dishes (from r=0.72 to r=0.79, P<0.001), confirming a good perception of the caloric discrepancies between food pictures. Two subgroups based on FCFQ followed by a principal component analysis (PCA) and a hierarchical ascendant classification (HAC) were defined, i.e. Prudent-type (PTc, N=9) vs. Western-type (WTc, N=7) consumers, where the WTc group showed higher consumption of high-energy palatable foods than PTc (P<0.05). The WTc group showed a higher correlation between liking and caloric evaluation of the food pictures as compared to PTc (r=0.77 and r=0.36 respectively, P<0.001), confirming that food pictures elicited variable responses according to contrasted individual eating habits. The fMRI analyses showed that the DL condition elicited the activation of dorsal Anterior Cingulate Cortex (dACC), involved in internal conflict monitoring, whereas SL condition did not, and that LE food choice involved high-level cognitive processes with higher activation of the hippocampus and fusiform gyrus compared to HE food choice. Overall, this pilot study validated the use of the food pictures database and fMRI-based procedure assessing decision-making processing during a food choice cognitive task with and without internal conflict.